1993
DOI: 10.1021/bi00066a036
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multiplex sequence analysis of mutational hot spots. Frequency and specificity of mutations induced by a site-specific ethenocytosine in M13 viral DNA

Abstract: We describe an assay for determining the frequency and specificity of mutations occurring at hot spots within a population of DNA molecules. The procedure consists of (a) annealing the DNA population with a labeled oligonucleotide designed to prime DNA synthesis at the mutational hot spot; (b) DNA elongation in the presence of a single dideoxynucleoside triphosphate together with 1-3 deoxynucleoside triphosphates, and (c) quantitation of all limit elongation products by high-resolution gel electrophoresis foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 14 publications
5
79
0
3
Order By: Relevance
“…Etheno-DNA adducts probably play a causal role in the initiation and progression of liver carcinogenesis. because they produce base pair substitution mutations; ⑀dA can lead to AT 3 CG, AT 3 TA, and AT 3 CG transversions 43,44 ⑀dC can cause CG 3 AT transversions and CG 3 TA transitions, 45,46 and N 2 ,3-ethenodeoxyguanosine, which is also formed in vivo from LPO products, can lead to GC 3 AT transitions. 46 These miscoding properties of etheno-bases strongly implicate them in the initiation of carcinogenesis by vinyl chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Etheno-DNA adducts probably play a causal role in the initiation and progression of liver carcinogenesis. because they produce base pair substitution mutations; ⑀dA can lead to AT 3 CG, AT 3 TA, and AT 3 CG transversions 43,44 ⑀dC can cause CG 3 AT transversions and CG 3 TA transitions, 45,46 and N 2 ,3-ethenodeoxyguanosine, which is also formed in vivo from LPO products, can lead to GC 3 AT transitions. 46 These miscoding properties of etheno-bases strongly implicate them in the initiation of carcinogenesis by vinyl chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection and preparation of pooled progeny phage DNA. The procedures employed for making E. coli cells competent for transfection of εC-DNA or C-DNA, for determining survival effects, and for preparing pooled progeny phage DNA have been described in detail elsewhere (46)(47)(48)(49)53).…”
Section: Methodsmentioning
confidence: 99%
“…The principles and experimental validation of multiplex DNA sequencing technology used to analyze mutation fixation at εC have been described in detail elsewhere (46)(47)(48) and are summarized in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etheno-adducts are highly promutagenic lesions; edA can lead to ATfiGC transitions as well as ATfiCG and ATfiTA transversions, 18,19 whereas edC can cause CGfiTA transitions and CGfiAT transversions. 18,20 Most sequence changes induced by MDA-DNA adducts are base pair substitutions, with 43% of these substitutions being G>T and 57% being C>T and A>G transversions. 21 Previous studies revealed that such oxidative, stress-related, miscoding etheno-DNA adducts increase in the hepatic tissue of liver cancer-prone patients.…”
mentioning
confidence: 99%